Protection of Trademarks from Unfair Competition Practices: A Comparative Study (Journal of human and social sciences, 2025)
The research examines the legal texts concerning the concept of trademarks and unfair competition claims under the provisions of Law No. (23) of 2010 on Libyan commercial activity, comparing it with Egyptian Law No. (82) of 2002 on the protection of intellectual property. The study concludes that there is a legislative gap in the Libyan legal framework, as unfair competition in the field of trademarks is limited to counterfeiting and imitation only. This limitation hinders comprehensive legal protection, since practices such as unauthorized use of others’ trademarks or importing them for commercial purposes also constitute unfair competition and cause similar harm. Unlike Libyan legislation, Egyptian law provides broader protection through general provisions that consider any action contrary to commercial norms and customs as unfair competition, offering greater flexibility. Accordingly, the study recommends that Libyan legislators adopt more comprehensive legal provisions covering a wider range of unfair competition practices to ensure efficient and adaptable legal protection in line with modern commercial challenges
Keywords: Trademark; Trademark Registration; Unfair Competition Practices; Libyan Legislation; Egyptian Legislation